Religion and poverty : Pan-African perspectives - Paris, Peter J., 1933-; Olupona, Jacob K. (Jacob Kẹhinde), 1951- (e-Duke books scholarly collection., 2009)
Examines religion-centered resistance strategies of the poor in Africa and its diaspora, analyzing the roots and structure of this poverty, religion's interaction with globalization and informal markets, and how the politics of social and economic amelior